Identification and structure activity relationships of quinoline tertiary alcohol modulators of RORγt. Issue 9 (1st May 2017) - Kummer, David A.; Cummings, Maxwell D.; Abad, Marta; Barbay, Joseph; Castro, Glenda; Wolin, Ronald; Kreutter, Kevin D.; Maharoof, Umar; Milligan, Cynthia; Nishimura, Rachel; Pierce, Joan; Schalk-Hihi, Celine; et al.
Graphical abstract: Abstract: A high-throughput screen of the ligand binding domain of the nuclear receptor retinoic acid-related orphan receptor gamma t (RORγt) employing a thermal shift assay yielded a quinoline tertiary alcohol hit. Optimization of the 2-, 3- and 4-positions of the quinoline core using structure-activity relationships and structure-based drug design methods led to the discovery of a series of modulators with improved RORγt inhibitory potency and inverse agonism properties.